Antimicrobial, Antioxidant and Other Pharmacological Activities of Ocimum Species: Potential to Be Used as Food Preservatives and Functional Ingredients. Issue 3 (3rd April 2023) - Sharifi-Rad, Javad; Adetunji, Charles Oluwaeun; Olaniyan, Olugbemi T.; Ojo, Stephen Kayode; Samuel, Micheal Olugbenga; Temitayo, Banjo Temitope; Roli, Osahon Itohan; Nimota, Olaogun Oluwatoyin; Oluwabunmi, Banjo Temitope; Adetunji, Juliana Bunmi; Sharopov, Farukh; Cruz-Martins, Natália; et al.
ABSTRACT: Ocimum plants are commonly used culinary herbs and fragrant ornamental plants. Beyond this feature, the present review firstly describes scientific studies on the antimicrobial and antioxidant activities of several Ocimum species. Secondly, the use of Ocimum plants as ingredients for food preservation, such as meat, fish and dairy products was covered. Thirdly, the phytochemical composition has been reviewed to reinforce further standardization to be Ocimum plants used as preservatives. Finally, other pharmacological properties (cardioprotective activity, anti-diabetic activity, hepato-renal protective activity, anticancer activity) are also reviewed. Overall, these plants can serve to promote food preservatives and functional ingredients, but there are still some challenges to be overcome as this review points out.